Pemberdayaan Masyarakat Melalui Pelatihan Pemasaran Online Bagi UMKM Desa Banjarsari – Gresik - Ferry Hariawan; Taudlikhul Afkar; Fauziyah; Teguh Purwanto (Ekobis Abdimas, 2022)
The aim of this community service activity program is to empower Micro, Small and Medium Enterprises (MSMEs) in the village of Banjarsari-Gresik through online marketing training of products that are characteristic of the area. This online marketing training is actually a continuation of the previous community service program that was carried out before the pandemic, for that now when the endemic is starting to be empowered again in the hope of increasing MSMEs income. This online marketing training technique was chosen because of the need and seeing the problems that occur. The intended need is to provide benefits to MSMEs actors so they can use online media, as well as problems that occur in the form of conventional marketing due to a lack of understanding of the use of online media for marketing. The results of this activity program show that there is enthusiasm for MSMEs actors to use online media in a simple way through applications that are closest to daily activities such as WhatsApp, Facebook, Instagram.